2018
DOI: 10.1158/1078-0432.ccr-17-0824
|View full text |Cite
|
Sign up to set email alerts
|

t-Darpp Activates IGF-1R Signaling to Regulate Glucose Metabolism in Trastuzumab-Resistant Breast Cancer Cells

Abstract: Increased glycolysis and glucose dependence is a hallmark of malignancy that enables tumors to maximize cell proliferation. In HER2 cancers, an increase in glycolytic capacity is associated with trastuzumab resistance. IGF-1R activation and t-Darpp overexpression both confer trastuzumab resistance in breast cancer. We therefore investigated a role for IGF-1R and t-Darpp in regulating glycolytic capacity in HER2 breast cancers. We examined the relationship between t-Darpp and IGF-1R expression in breast tumors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Several studies have demonstrated that DARPP-32 and t-DARPP protect cancer cells from drug-induced apoptosis, which is dependent upon their T75 phosphorylation residue 9 , 10 and involves upregulation of Akt and Bcl2 proteins 16 , 18 , 19 . Most recently, t-DARPP overexpression was shown to promote activation of insulin-like growth factor-1 receptor signaling to regulate glucose metabolism as a mechanism of trastuzumab resistance in breast cancer cells 20 . To date, the role of DARPP-32 isoforms in lung cancer remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that DARPP-32 and t-DARPP protect cancer cells from drug-induced apoptosis, which is dependent upon their T75 phosphorylation residue 9 , 10 and involves upregulation of Akt and Bcl2 proteins 16 , 18 , 19 . Most recently, t-DARPP overexpression was shown to promote activation of insulin-like growth factor-1 receptor signaling to regulate glucose metabolism as a mechanism of trastuzumab resistance in breast cancer cells 20 . To date, the role of DARPP-32 isoforms in lung cancer remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…To meet with the need of rapid cell growth, the key regulators of glycolysis, such as glucose transporters (GLUTs) and glycolytic enzymes, are usually overexpressed in cancer cells. It has been documented that insulin stimulated glucose metabolism via insulin growth factor receptor (IGF-1R), consequently activating the phosphorylation of AKT and up-regulated the expression of GLUTs [22][23][24]. IGF-1R and AKT-GLUT1 axis might be promising targets of miRNAs to affect the progression of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Co-targeting of the IGF-IR and EGFR axes may therefore provide an efficacious therapeutic strategy for GBM (24). It may also be relevant to brain metastases originating from other malignancies, such as breast cancer (60).…”
Section: Discussionmentioning
confidence: 99%